Analisis Perkembangan E-Wallet Sebagai Alat Pembayaran UMKM di Bagian Bendahara Barang Kantor Walikota Medan - Muhammad Rivaldi Pane; Nurhayati Nurhayati (Universitas Muhammadiyah Enrekang, 2022)
This study aims to analyze the development of E-Wallet as a means of payment for MSMEs in the Treasurer of the Medan Mayor's Office. This study uses a qualitative method, which in this method uses a literature study approach. Literature study is an activity to obtain data through reading and taking notes and then managing the data both through books and scientific journals. Then, plus observations or direct observations made by researchers during internships as well as conducting interviews with employees in the goods treasury which resulted in the conclusion that E-wallet plays an important role in conducting transactions, facilitates and is very helpful for MSMEs in the goods operations section of the Medan Mayor's Office.